A case of dermatomyositis with rhabdomyolysis, rescued by intravenous immunoglobulin. Issue 4 (July 2015) - Mizoguchi, Fumitaka; Takada, Kazuki; Ishikawa, Kinya; Mizusawa, Hidehiro; Kohsaka, Hitoshi; Miyasaka, Nobuyuki
Abstract: We describe a case of severe dermatomyositis (DM) complicated by rhabdomyolysis, acute tubular necrosis, and hemophagocytosis. The case failed to respond to corticosteroids, but showed rapid and significant improvement after the addition of intravenous immunoglobulin (IVIG). While the prognosis of DM is poor when it is complicated by rhabdomyolysis, the early administration of IVIG has the potential to be the cornerstone of its management.